A parametric study of a monolithic microfluidic system for on-chip biomolecular separation - Chan, A.; Danquah, Michael; Agyei, D.; Hartley, P.; Zhu, Y. (Taylor and Francis, 2014)
A microfabricated poly(dimethylsiloxane) (PDMS) chip containing channel filled with polymer monolith has been developed for on-chip biomolecule separation. Methacrylate monolithic polymers were prepared by photo-initiated polymerization within the channel to serve as a continuous stationary phase. The monolithic polymer was functionalized with a weak anion-exchange ligand, and key parameters affecting the binding characteristics of the system were investigated. The total binding capacity was unaffected by the flow rate of the mobile phase but varied significantly with changes in ionic strength and pH of the binding buffer. The binding capacity decreased with increasing buffer ionic strength, and this is due to the limited available binding sites for protein adsorption resulting from cationic shielding effect. Similarly, the binding capacity decreased with decreasing buffer pH towards the isoelectric point of the protein. A protein mixture, BSA and ovalbumin, was used to illustrate the capacity of the methacrylate-based microfluidic chip for rapid biomolecule separation.